1984
DOI: 10.1557/proc-44-623
|View full text |Cite
|
Sign up to set email alerts
|

Gamma and Alpha Radiolysis of Salt Brines

Abstract: Gamma radiolysis of Permian Basin brine leads to equilibrium gas pressure of about 100 atm. at 75°C and about 40 atm. at 150°C, providing the gas space is very small and/or the total dose is very high. Dose rate dependence is being investigated but is not yet established. Alpha radiolysis of Permian Basin brine is still being evaluated, but it is clear that equilibrium gas pressures will be much higher than with gamma radiolysis. In addition, alpha radiolysis of brine results in a very high solution redox pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…LET for α particles decreases with energy that is greater than 1.5 MeV. G (hydrogen) values for irradiated water and aqueous salt solutions are often controlled by a back-reaction of hydrogen with the OHá radical to form water (Gray and Simonson 1984). Hyder and others (1998) recently published a literature review pertinent to core technology research for the 94-1 Research and Development Project on recombination of water.…”
Section: Liquid Watermentioning
confidence: 99%
See 3 more Smart Citations
“…LET for α particles decreases with energy that is greater than 1.5 MeV. G (hydrogen) values for irradiated water and aqueous salt solutions are often controlled by a back-reaction of hydrogen with the OHá radical to form water (Gray and Simonson 1984). Hyder and others (1998) recently published a literature review pertinent to core technology research for the 94-1 Research and Development Project on recombination of water.…”
Section: Liquid Watermentioning
confidence: 99%
“…However, the presence of impurities dissolved in water (such as Brø, Clø, which act as scavengers of the OHá radical) will increase the yield of hydrogen in the gas phase (BŸppelmann et al 1988, Gray andSimonson 1984). Moreover, some researchers have suggested that the G (hydrogen) values and equilibrium concentrations of hydrogen are controlled by a back-reaction of hydrogen with the OHø to form water Orebaugh 1977, Gray andSimonson 1984).…”
Section: Liquid Watermentioning
confidence: 99%
See 2 more Smart Citations
“…As compared with the results of similar ex periments under room temperature and atmospheric pressure conditions (Table 1), where approximately equal gamma-ray doses are absorbed by water samples, the rise of temperature promotes the ef (Gray and Simonbon, 1984). The hematitization alteration, an enhance ment of ferric iron contents, of the wall-rocks in hydrothermal uranium deposits is thus expected to be more developed than that in the leaching accumulative and sedimentary-diagenetic uranium deposits.…”
Section: Resultsmentioning
confidence: 83%